the PROBLEMS FACE BY THE UNIVERSITY RESEARCHERS DURING COVID-19 - SABA SARWAR; GHULAM HAIDER (Innovare Journal of Social Sciences, 2024)
Coronavirus disease 2019 (COVID-19’s) explosion has posed a serious danger to global economic activity and it has made life particularly tough for research institutes. The global spread of COVID-19 is continuing to have a significant impact, making it difficult to strike a balance between personal safety and work responsibilities. Most research scientists have had to deal with a variety of unforeseen challenges. This is primarily due to a lack of tools and challenges connected to managing personal security and family obligations during this time. The objective of this research paper was to find the problems faced by university researchers during the COVID-19 pandemic. The study was qualitative in nature. Social sciences and pure sciences faculties were part of the sample. An interview was scheduled with M.Phil and Ph.D students from the city of Faisalabad for data collection purposes. Simple random sampling was employed. Results of the study show that there were numerous problems such as data collection, research tools, access to the laboratories, internet resources, residence in hostels as well as transportation issues that the university researchers faced in their research work during COVID-19.